Dermatitis Eksfoliatif Generalisata - Muhammad Iqbal Maulana; Wizar Putri Melaratna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Generalized exfoliative dermatitis, also known as erythroderma, is a skin disease with dermatological features in the form of diffuse erythema and scaling that affects more than 90% of the skin surface. This report describes the case of a 65 year old man who came with the main complaint, the skin all over his body felt itchy and peeling since approximately 2 years ago. The itching experienced by the patient worsens during hot weather/temperature, usually occurring during the day and night, but the itching experienced is more severe at night. The patient's complaints began with the appearance of redness on the skin in the left and right hand area, then spread to the chest area, groin/genital area, both legs, and throughout the body up to the head. Dermatological status examination revealed diffuse erythema macules accompanied by rough scales all over the body. The patient was diagnosed with generalized exfoliative dermatitis. In management, patients are given education to maintain skin moisture, avoid scratching the skin, and consume foods high in protein such as red meat. The pharmacological management given is in the form of corticosteroid drugs, antibiotics, proton pump inhibitors, antihistamines, and several topical drugs to reduce complaints of itching and peeling skin in patients.